Penggunaan Google Form Sebagai Alat Evaluasi Pembelajaran di Sekolah Menengah Pertama Negeri 36 Sarolangun - Wildan Ahmad Rauf; Shalahudin Shalahudin; Sodiah Sodiah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the use of Google Forms as a learning evaluation tool at State Junior High School 36 Sarolangun. It also aims to identify obstacles to using Google Forms as a learning evaluation tool and to identify solutions to overcome these obstacles. This study used a descriptive qualitative approach at State Junior High School 36 Sarolangun. Data collection techniques included observation, interviews, and documentation. Forecasting sampling was used as a method for selecting informants. The results indicate that the use of Google Forms as a learning evaluation tool has been well-used by teachers, although implementation challenges exist, such as limited features, potential cheating, technical issues, and data privacy. Solutions to overcome these obstacles include ensuring a stable internet connection, providing alternatives for students without internet access, and checking browser and device settings. To address test design, divide the questions into sections, set time limits, use the random question feature, provide clear feedback, and involve students in the evaluation process.